Mendukung UMKM Desa Candiwatu: Melalui Legalitas Usaha dan Branding Tape Ketan Hitam - Fariska Nikmatus S; Luthfiyah, Nafa Hikmatul; Jeffry Wahyu Eka P; Nadia, Dinda; Sri Diyanti, Daffa Dwi (Yayasan Cendekia Gagayunan Indonesia, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in the Indonesian economy, particularly in rural areas. Candiwatu Village in Mojokerto Regency is known as a production center for Black Sticky Rice Tape, a traditional culinary product with high cultural and economic value. However, most MSMEs in this village lack adequate understanding of business legality and the importance of visual identity in marketing their products. This guidebook was developed as a form of assistance focused on increasing legal awareness through copyright registration and strengthening branding through collaborative logo design. Through a participatory approach, this book provides practical and applicable guidance that can be used by MSMEs, students, and village officials to encourage the growth of legal, independent, and competitive local MSMEs. The results of the assistance show that legal protection of intellectual property and strong branding are two complementary aspects in enhancing the position of MSMEs in an increasingly competitive market.